Dimensional Psychopathology - Biondi, Massimo; Pasquini, Massimo; Picardi, Angelo (SpringerLink Bücher, 2018)
Foreword -- Preface -- The Rapid Dimensional Assessment Scale (RADAS): development and applications in research -- Dimensional assessment with RADAS in clinical practice -- The Fear/Apprehension and Somatization/Somatic Preoccupation dimensions (psychic and somatic anxiety dimensions) -- The Reality Distortion and Thought Disorganization dimensions -- Violence and compulsory treatment in the psychiatric setting -- The Sadness, Demoralization and Apathy dimensions -- The “outer dimensions” Activation, Impulsivity, Anger/Aggressiveness -- The Obsessive–compulsive dimension -- Psychopathological dimensions and the clinician’s subjective experience: a quantitative analysis -- The temporality dimension. .